Mary Jiménez: íntima y universal - Bustamante, Emilio (Pontificia Universidad Católica del Perú. Fondo Editorial, 2018)
The present article highlights peruvian filmmaker Mary Jiménez as a pioneer of the first person documentary in Latin America, and intents to prove that in her work there is an intention to meet with the Other and reintegrate the individual with the universe.

El presente artículo destaca a la cineasta peruana Mary Jiménez como pionera de los documentales del yo en América Latina y constata en su obra una intención de reunión con el otro y de re-integración del individuo con el universo.
Mary Jiménez: Intimate and Universal
Keywords: Cine; Cine peruano; Documental; https://purl.org/pe-repo/ocde/ford#5.09.01